(untitled) (European Journal of Formal Sciences and Engineering, 2020)
The study defines the advent of new technologies such as electronic contract and Electronic signature and other networks that have had impanct in changeing the business world wide and provided the trading processes in e-business more efficiency. In this article we will discuss about Electronic Constract and Electronic Signature in developed countries, how they have regulated this issue and when did it started to be used, wich do the positive and negative aspects, where Kosovo can benifite, know that in Kosovo is still not regulated with a law. We will focus on meeting the needs of the community in kosovo to have a law that Regulats the use of Electronic Contracts and Electronic Signature and trying to solve their problems in doing business world wide.